2006
DOI: 10.1111/j.1365-246x.2006.02897.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging subduction from the trench to 300 km depth beneath the central North Island, New Zealand, withVpandVp/Vs

Abstract: S U M M A R YRecent dense deployments of portable digital seismographs have provided excellent control on earthquakes beneath the central North Island of New Zealand. Here we use a subset of the best-recorded earthquakes in an inversion for the 3-D Vp and Vp/Vs structure. The data set includes 39 123 P observations and 18 331 S observations from 1239 earthquakes and nine explosions. The subducted plate is imaged as a high Vp, low Vp/Vs feature. Vp within the mantle of the subducted slab is almost always >8.5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
316
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(349 citation statements)
references
References 77 publications
(99 reference statements)
31
316
2
Order By: Relevance
“…A similar B10-km thick crust-mantle transition layer with lower seismic velocities (that is, Vp ¼ 7.0-7.7 m s À 1 ) has also been identified beneath the Izu-Bonin-Mariana and Tonga arcs, interpreted to be composed of a mixture of crustal and mantle materials 45,46 . Likewise, beneath the central Taupo Volcanic Zone, a zone of reduced seismic velocities of ZVp ¼ 7.4 m s À 1 (Vp/Vs ¼ B1.87) extends from the Moho to the slab-mantle wedge interface suggesting diapirically rising hydrated and low density material 47 . Lower seismic velocities of Vp ¼ B7.7, (and density ¼ B3.0 g cm À 3 ; Vp/Vs ¼ B1.85), which are similar to the velocities observed at the crust-mantle boundary beneath arcs have been measured in exhumed subduction mélange rocks with compositions intermediate between chlorite schists and jadeite (at T ¼ 600°C and P ¼ 2 GPa).…”
Section: Resultsmentioning
confidence: 99%
“…A similar B10-km thick crust-mantle transition layer with lower seismic velocities (that is, Vp ¼ 7.0-7.7 m s À 1 ) has also been identified beneath the Izu-Bonin-Mariana and Tonga arcs, interpreted to be composed of a mixture of crustal and mantle materials 45,46 . Likewise, beneath the central Taupo Volcanic Zone, a zone of reduced seismic velocities of ZVp ¼ 7.4 m s À 1 (Vp/Vs ¼ B1.87) extends from the Moho to the slab-mantle wedge interface suggesting diapirically rising hydrated and low density material 47 . Lower seismic velocities of Vp ¼ B7.7, (and density ¼ B3.0 g cm À 3 ; Vp/Vs ¼ B1.85), which are similar to the velocities observed at the crust-mantle boundary beneath arcs have been measured in exhumed subduction mélange rocks with compositions intermediate between chlorite schists and jadeite (at T ¼ 600°C and P ¼ 2 GPa).…”
Section: Resultsmentioning
confidence: 99%
“…10b). Reyners et al (2006) Taken together, slow earthquake observations, thermal modeling and seismic velocity models indicate that temperature may be the main factor controlling the depth and lateral extent of the seismogenic zone at the Hikurangi margin . In the northeast, the higher slab temperatures and fluid generation (with inferred high pore-fluid pressure) lower the depth to the brittle-ductile transition, as well as the depth of unstable to stable sliding, compared to the southwest.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…There is an abundance of high-resolution three-dimensional regional velocity models from P-and S-wave travel-time tomography studies (Eberhart-Phillips and Reyners, 2012;Reyners et al, 2006); in comparison, teleseismic scattering studies of the Hikurangi margin are sparse. Henrys et al (2013) showed P-wave velocity structure of the forearc system from the active source data beneath the southern North Island.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…1) is thought to overlie the juxtaposition of a thin continental crust (25 km) to the north against a normal thickness crust (36 km) to the south (Stern et al 1987), which is marked by the Taranaki-Ruapehu Line (TRL). From the orientation of the regional gravity anomaly, Stern et al (1987) considered the TRL to be aligned east-west, although Reyners et al (2006), using 3D velocity tomography results, think it is aligned northwest-southeast, parallel to the dip of the subducting Pacific plate beneath the North Island. Although the area is seismically active (Sherburn & White 2005), there are no known active faults, possibly because the earthquakes are concentrated deeper than 25 km below the surface (Sherburn & White 2005).…”
Section: Introductionmentioning
confidence: 99%